2013
DOI: 10.1016/j.brainres.2013.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb amputation-induced reorganization in the cuneate nucleus (CN) is not reflected in large-scale reorganization in rat forepaw barrel subfield cortex (FBS)

Abstract: We examined reorganization in cuneate nucleus (CN) in juvenile rat following forelimb amputation (n=34) and in intact controls (n=5) to determine whether CN forms a substrate for large-scale reorganization in forepaw barrel subfield (FBS) cortex. New input from the shoulder first appears in the FBS 4 weeks after amputation, and by 6 weeks, the new shoulder input comes to occupy most of the FBS. Electrophysiological recording was used to map CN in controls and in forelimb amputees during the first 12 weeks foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…In the present study in adult rats, it is possible that primary afferents from the shoulder invaded the deafferented forepaw zone in CN but were functionally unexpressed. Similar findings of a mismatch between the appearance of sprouted hindlimb afferents into CN and their functional expression have been reported (Rhoades et al, 1993); however, even at 30 weeks after amputation, few cells in the central zone in CN responded to input from the shoulder, and those were localized to the outer region bordering the forepaw zone (Li et al, 2013). …”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In the present study in adult rats, it is possible that primary afferents from the shoulder invaded the deafferented forepaw zone in CN but were functionally unexpressed. Similar findings of a mismatch between the appearance of sprouted hindlimb afferents into CN and their functional expression have been reported (Rhoades et al, 1993); however, even at 30 weeks after amputation, few cells in the central zone in CN responded to input from the shoulder, and those were localized to the outer region bordering the forepaw zone (Li et al, 2013). …”
Section: Discussionsupporting
confidence: 74%
“…While we and others suggest that the resulting SI reorganization that follows deafferentation depends on subcortical changes (Garraghty and Kaas, 1991; Li et al, 2013; Pearson et al, 2001; Rasmusson, 1996b; Stojic et al, 1998), this conclusion is not without exception (Darian-Smith and Gilbert, 1995). Previously we reported that following forelimb amputation, new input was first observed in FBS within 4 weeks after amputation and by 6 weeks, new shoulder responses could be recorded throughout most of the FBS (Pearson et al, 2003).…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations